(untitled) (International Journal of Physiotherapy, 2014)
Background: People with vestibular dysfunction complain of problems with balance and dizziness which creates a negative impact on the people and affects their quality of life. Medications help in the control of symptoms. There has been an increase in the implementation of many protocols for the rehabilitation of vestibular patients with follow up exercises for the treatment of BPPV. Methods: Thirty BPPV patients were identified by doing Dix- Hall pike positioning and their DHI scores were recorded. All patients were exclusively treated with Semont Liberatory maneuver. The effectiveness of the treatment was documented at 1 week and 1 month. Repeated procedures were performed if necessary. Results: After the treatment session of Semont Liberatory maneuver, the symptoms disappeared in 20 patients and have negative DHI test by 1st week, and of patients have negative DHI test by 1 month. The first success rate was 78% and the total success rate was 89%. Semont Liberatory maneuver also showed decrease in score of DHI [post-test] in 1 month duration. The patient who visited within one week after the onset of symptoms had good prognosis with Semont Liberatory maneuver. This protocol was ineffective in 4 patients. Conclusion: The Semont Liberatory maneuver is a safe and effective technique for treating BPPV patients.